"Um olhar para você": o autocuidado de profissionais de saúde mental durante a pandemia de COVID-19 - Cunha, Matheus Vieira da (2023)
The abrupt emergence of the New Coronavirus (Covid-19), resulting from the Sars-CoV-2 virus, in 2019, raised profound questions on an individual and global level regarding mental health, specifically modifying lifestyles and habits, requiring adaptations to a new daily life. Due to the pandemic, there was an increase in demand and overload for mental health care services. Considering the problem, self-care in mental health professionals is a field of study little addressed in the country. In this sense, this study aims to understand self-care actions of mental health professionals at Psychosocial Care Centers (CAPS) during the Covid-19 pandemic. To this end, two studies were developed: i) scoping review that included 129 studies published between 2020 and 2022 in the Journal of the Coordination for the Improvement of Higher Education Personnel (CAPES), and guided by the question: “How has scientific literature addressed self-care of health professionals during the Covid-19 pandemic?”; and ii) semi-structured interviews with six mental health professionals from the Psychosocial Care Centers (CAPS), Ilha de Santa Maria (CAPS II) and São Pedro (CAPS III), in the municipality of Vitória/ES. About the data, these were guided, treated and detailed by the PRISMA-ScR Checklist scoping review guide (Study 1) and Content Analysis (Study 2). The adverse context caused by Covid-19 brought suffering of different orders and levels to study professionals, from anguish and discomfort, to depressive, anxious and post-traumatic conditions. National and international literature indicates that self-care practices, behaviors and management during the Covid-19 pandemic crisis resulted in improvements in different levels of health and physical and mental well-being in the research population, mainly associated with protective factor for mental health. The research contained in the literature review, in turn, cites Mindfulness, Integrative Health Care Practices (PICS) and the support network at work as self-care strategies. After the interventions, professionals continued the practices, in line with gains in physical and mental health, with positive results in resilience and self-compassion. As a limitation, careful detail regarding the nature of the relationship between self-care and resilience and studies that deepen and equally relate PICS practices to self-care. As for the professionals' narratives, the results showed fear and acceptance in the face of exposure to the virus, culminating in anguish, emotional exhaustion and stress, perceptions, feelings and sensations of the most critical moments of the pandemic that are currently impacting. After countless transformations, with a change in the nature of the service and high demand, care was implemented in the dimension of team meetings, marked by the sharing of anxieties and difficulties, in addition to the change in working hours that made it possible to introduce self-care activities: social, physical care and mental health, medical consultations, yoga, healthy eating, meditation and art therapy. These were related to improvements in health and quality of life indicators, such as emotional and mental balance and completeness in self-knowledge processes.